PERAN DAN KONTRIBUSI PENDIDIKAN AGAMA ISLAM: PEMBERDAYAAN PEREMPUAN DENGAN KESETARAAN GENDER ANTARA LAKI-LAKI DI LINGKUNGAN MASYARAKAT - Rohman, Nuri Azizi; Khafidhoh, Nour; Astuti, Nita Yuli (Taklim : Jurnal Pendidikan Agama Islam, 2024)
AbstractThrough the latest approaches in the social, economic and political fields, the latest research shows that Islamic religious education can provide a strong foundation for women to develop their potential and achieve gender equality. This research aims to explore the important role of Islamic religious education in empowering women socially, economically and politically, as well as providing a deeper understanding of its contribution to increasing women's participation in society. The research method used is literature research to analyze the role of Islamic religious education in empowering women, including access to education, employment opportunities, health, involvement in political and social decisions in the Islamic religion. Islamic religious education, which is closely related to the teachings of the Koran and hadith as a guide to life and behavior since ancient times, has played an important role in equality between men and women. Apart from that, Islamic religious education also helps overcome stereotypes and norms that limit women.Keywords: Role and Contribution, Islamic Education, Women Empowerment, Gender Equality, Community EnvironmentAbstrakMelalui pendekatan terkini dalam bidang sosial, ekonomi, dan politik, penelitian terbaru menunjukkan pendidikan agama Islam dapat memberikan landasan kuat bagi perempuan dalam mengembangkan potensi mereka dan mencapai kesetaraan gender. Penelitian ini bertujuan untuk mengeksplorasi peran penting pendidikan agama Islam dalam memberdayakan perempuan secara sosial, ekonomi, dan politik, serta menyediakan pemahaman yang lebih mendalam tentang kontribusinya dalam meningkatkan partisipasi perempuan dalam kehidupan masyarakat. Metode penelitian yang digunakan merupakan penelitian kepustakaan untuk menganalisis tentang peran pendidikan agama Islam dalam memberdayakan perempuan, termasuk dalam akses pendidikan, kesempatan kerja, kesehatan, keterlibatan dalam keputusan politik dan sosial dalam agama islam. Pendidikan agama islam yang erat kaitannya dengan ajaran Al-Qur’an serta hadis sebagai pedoman dalam kehidupan. Kata kunci : Peran dan Kontribusi, Pendidikan Islam, Pemberdayaan Perempuan, Kesetaraan Gender, Lingkungan Masyarakat